Treating binge eating problems in primary care. - Carter, J; Fairburn, C (1995)
Binge eating problems are a common source of psychiatric morbidity among young adult women. To date, the research on their treatment has been conducted almost exclusively in specialist settings. As it is unlikely there will ever be sufficient specialist resources to address a problem of this scale, a priority is to develop treatments that can be applied more generally. One option is to develop treatments suitable for use in primary care. Four such treatments are available: antidepressant drugs, brief cognitive behavior therapy, and the use of a cognitive behavioral self-help manual with or without supervision from a nonspecialist therapist. Tests of the effectiveness of these treatments are needed.